Interdisciplinary Learning Opportunities for Clinical Students and Teachers - A Case Study Shared - Katia Ferrar; Liz Curran; Matthew Atkinson; Paraskevi Kontoleon
This article considers the value of interdisciplinary learning by examining the experiences of staff and students involved in a pilot health justice student-delivered clinic at the University of South Australia By analysing the pilot clinic, this article argues that successful interdisciplinary learning requires integration of knowledge from various disciplines around an overarching topic or theme (in this instance, homelessness and access to justice) that guides the educational experience. This collaborative approach is posited to provide enhanced student outcomes and improve attitudes towards interprofessional teamwork which may increase student willingness to work in an interdisciplinary environment when they graduate. The article further suggests that curriculum enhancement through interdisciplinary opportunities can better position students and staff supervisors as health and legal practitioners by breaking down professional misunderstandings and improving outcomes for the community.